Acoustic Coupled Disaster & Remote Communications Systems - Müller-Baumgart, Ulf; Gardner-Stephen, Paul; Bettison, Andrew; Challans, Romana; Lakeman, Jeremy (Journal of Telecommunications and the Digital Economy, 2020)
Following disasters, and in other infrastructure-deprived settings, such as remote areas, the need for communications is profound. However, the ability to provide communications solutions in such situations is extremely difficult because of the lack of functional infrastructure, and the logistical difficulty or impossibility of bringing in additional hardware. Therefore it is important to create communications solutions that can operate using existing locally available hardware. In this paper we describe one possible solution based on acoustic coupling of mobile telephones with existing two-way radios, such as are often carried in remote areas of Australia, and are fitted to many vehicles that are used in such areas. We describe a number of related software systems and some simple experiments that demonstrate the feasibility of the general concept, before describing a possible integration of such technologies with the secure digital communications capabilities offered by the open-source Serval Mesh software. We argue that such an integration is not only possible, but also has the potential to allow secure digital communications in a variety of scenarios, without the need for any new or additional hardware.